A Study of the Linguistic Features of Suggestion Verbs in English and Their Vietnamese Equivalents - Nguyễn Thị Xuân Thứ (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
It is clearly true that suggestion verbs have their own characteristics in relation with diversified structures and meaning nuances. This study was designed to investigate English suggestion verbs and their Vietnamese equivalents in terms of their syntactic and semantic features. The descriptive and contrastive methods were employed to give a detailed description of some linguistic features of suggestion verbs and to point out the similarities and differences between English suggestion verbs (ESVs) and Vietnamese suggestion verbs (VSVs) in the above mentioned aspects. In addition, the findings of this study were clearly presented based on a collection of 300 samples of English and Vietnamese suggestion verbs which are taken from short stories by English and American writers and some well- known magazines, namely Special English, Special News and Sunflower. It is hoped that the results of this study will probably provide some practical suggestions for the teaching and learning of English by Vietnamese people.